Biocarriers facilitated gravity-driven membrane (GDM) reactor for wastewater reclamation : effect of intermittent aeration cycle - Lee, Seonki (2021)
This study investigated the performances of gravity-driven membrane (GDM) reactors integrated with granule activated carbon (GAC) biofilm process for wastewater treatment under different intermittent aeration cycles (intensity and frequency). The results showed the removal efficiencies of dissolved organic carbon, total nitrogen, ammoniawere significantly improved under intermittent aeration conditions (~86–87%, ~29–37%, and ~83–99%, respectively) compared to non-aeration condition (~72% and ~18%, and ~17%, respectively). In addition, it was found that the intermittent aeration significantly reduced the cake layer resistance and therefore improved ~130–300% the permeate flux compared to control without aeration. Microbial community analysis indicated that prokaryotic and eukaryotic compositions in the cake layer biofilm were significantly influenced by aeration condition. Lastly, energy consumption analysis revealed that GAC + GDM with shorter aeration period and low aeration intensity could be promising as a decentralizedwastewater treatment process in terms of water quality and operating energy.